1998
DOI: 10.21273/hortsci.33.4.672
|View full text |Cite
|
Sign up to set email alerts
|

Flowering of Herbaceous Perennials under Various Night Interruption and Cyclic Lighting Treatments

Abstract: Six long-day species of herbaceous perennials were grown under six night-interruption (NI) photoperiod treatments to determine their relative effectiveness at inducing flowering. Photoperiods were 9-hour natural days with NI provided by incandescent lamps during the middle of the dark period for the following durations: 0.5, 1, 2, or 4 hours; 6 minutes on, 54 minutes off for 4 hours (10% or 6/54 cyclic lighting); or 6 minutes on, 24 minutes off for 4 hours (20% or 6/24 cyclic lighting). For five specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
27
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 0 publications
6
27
0
Order By: Relevance
“…This phenomenon has also been reported with other species (Grossin and Mathon, 1961;Lang, 1965). Similarly, Runkle et al (1998a) found that the saturation duration of NI for 'Goldsturm' decreased from 4 to 1 h following 8 weeks of cold. A cyclic lighting regimen, 6 min on and 24 min off for 4 h (20% or 6/24 cyclic lighting), was as effective as a continual 4-h NI for cooled plants, but not for noncooled plants (Runkle et al, 1998a).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…This phenomenon has also been reported with other species (Grossin and Mathon, 1961;Lang, 1965). Similarly, Runkle et al (1998a) found that the saturation duration of NI for 'Goldsturm' decreased from 4 to 1 h following 8 weeks of cold. A cyclic lighting regimen, 6 min on and 24 min off for 4 h (20% or 6/24 cyclic lighting), was as effective as a continual 4-h NI for cooled plants, but not for noncooled plants (Runkle et al, 1998a).…”
Section: Discussionsupporting
confidence: 86%
“…In agreement with Yuan (1995) and Runkle et al (1998a), but not Nau (1996), a cold treatment was not required for flowering of 'Goldsturm' but did hasten time to flower by ≈35%. Application of a cold treatment also reduced the number of new nodes developed below the first inflorescence.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…We reported the sensitivity of E . purpurea ‘Bravado’ to short (30 min) durations of NI (Runkle et al 1998). To our knowledge, no NI studies have been performed on any other IDP.…”
Section: Discussionmentioning
confidence: 99%
“…The FR response is supported by many studies in which NI and day‐extension (DE) lighting containing R and FR more effectively induce flowering (i.e., flowering is more complete and rapid) than light deficient in FR. Some exceptions exist: Whitman et al (1998) found that lamps with various R:FR (from 0.7 to 8.8) induced flowering similarly in 3 species that Runkle et al (1998) found were light‐dominant LDP. Nevertheless, in many LDP, FR light simultaneously promotes flowering (through light‐labile phytochrome) and stem extension (through light‐stable phytochrome).…”
Section: Introductionmentioning
confidence: 99%